A STUDY OF THE DEVELOPMENT OF DIFFERENT FORMS OF ORGANIZATION OF INNOVATIVE ACTIVITY IN THE SPHERE OF HIGH TECHNOLOGIES - S. Hahanov (Вестник университета)
The article presents the results of research of various forms of organization of innovative activity in the sphere of high technologies, revealed their features and short characteristic given. The proposed approach makes it possible to determine the place and the role of technoparks in the innovation economy.